2023
DOI: 10.3390/cryst13081174
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Stability of NiO/Ga2O3 Vertical Heterojunction Rectifiers

Abstract: The stability of vertical geometry NiO/Ga2O3 rectifiers during two types of annealing were examined, namely (1) the annealing of NiO only, prior to the deposition of the Ni/Au metal anode stack, and (2) the annealing of the completed device. The devices were annealed in oxygen for 1 min at a temperature of up to 500 °C. The results show that annealing at 300 °C can lead to the best performance for both types of devices in terms of maximizing the breakdown voltage and on–off ratio, lowering the forward turn-on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Gong et al [52] and Yan et al [56] both observed interface states in the order of ~10 10 eV −1 cm −2 , which are among the lowest reported values. In addition, Li et al [57] The anisotropic nature of NiO x /β-Ga 2 O 3 in different crystal orientations has also been investigated. Deng et al [54] investigated the dependence of the band alignment of NiO x /β-Ga 2 O 3 heterostructures on various crystal orientations and revealed differences in the conduction and valence band offsets.…”
Section: P-nio X /β-Ga 2 O 3 Heterojunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gong et al [52] and Yan et al [56] both observed interface states in the order of ~10 10 eV −1 cm −2 , which are among the lowest reported values. In addition, Li et al [57] The anisotropic nature of NiO x /β-Ga 2 O 3 in different crystal orientations has also been investigated. Deng et al [54] investigated the dependence of the band alignment of NiO x /β-Ga 2 O 3 heterostructures on various crystal orientations and revealed differences in the conduction and valence band offsets.…”
Section: P-nio X /β-Ga 2 O 3 Heterojunctionmentioning
confidence: 99%
“…Gong et al [52] and Yan et al [56] both observed interface states in the order of ~10 10 eV −1 cm −2 , which are among the lowest reported values. In addition, Li et al [57] demonstrated the thermal annealing stability of NiO x /β-Ga 2 O 3 p-n diodes from 300 to 500 • C in comparison with the as-deposited NiO x /β-Ga 2 O 3 p-n diodes. Annealing at 300 • C resulted in a reduced low forward bias current, while the specific on-resistance (R on,sp ) remained relatively stable.…”
Section: P-nio X /β-Ga 2 O 3 Heterojunctionmentioning
confidence: 99%
See 1 more Smart Citation